PEMBELAJARAN ERA PANDEMI COVID-19 BERKARAKTERISTIK REALISTIC MATHEMATICS EDUCATION PADA KETERCAPAIAN KEMAMPUAN PEMAHAMAN GEOMETRIS SISWA KELAS VII - Riajanto, Marchasan Lexbin Elvi Judah (IKIP Siliwangi, 2021)
Obstacles in learning in the era of the Covid 19 pandemic appear real and it is natural because of unpreparedness for situations that suddenly change. But in line with the necessity for the continuity of education which includes, among other things, the necessity of continuing learning, the only option available is an option, namely distance learning. This study aims to analyze the achievement of students' geographical abilities during the COVID-19 pandemic. The research subjects were Grade VIII students of the 2020/2021 school year from two classes at SMPN Cianjur, West Java, totaling 86 students. The test instrument used in this study was a description test that measured the mechanical understanding ability of grade VII students. The results of this study were students 'achievement in geometric comprehension ability was still very low, seen from the students' achievement scores, almost all of them were below 0.30. The conclusion of this study is that the achievement of low mathematical abilities or the low level of mastery of students' mathematical concepts is a problem that must be taken seriously which, among others, can be done by developing learning.